Representações de enfermeiros(as) da Atenção Primária à Saúde sobre sexualidade no contexto da prevenção das infecções sexualmente transmissíveis/HIV - Sheila Milena Pessoa dos Santos (2019)
In the axis of integrality of health care, sexuality is an important component in the care provided by professionals, both individually and collectively. The sexuality approach is essential for health practitioners to understand the ways in which caregivers as well as the population interpret the risk and prevention of diseases related to sexual activity and sexual health in the breadth of the law provided for regulations of the health sector. On the contrary way to the logic of integral care, there is the incipient focus of sexuality in the daily life of services, including nursing care. This fragility in health care justifies the need to investigate the processes that guide nurses' practices and that make it difficult to introduce sexuality issues in care practices. In this study, we sought to explore the gap in primary health care in the field of STI / HIV prevention and control. The general objective of the study was to understand the representation of primary care nurses on sexuality, especially in STI/ HIV care, and the specific objectives were 1/ To interpret the representations about sexuality from Nurses’ narratives about personal and professional experiences; 2/ To analyze the presence of these representations in the primary health care, in relation to the prevention of STI/HIV, from nurses’ viewpoint. This is a qualitative study, anchored in the critical axis of the Theory of Social Representations, based on the perspective proposed by Alain Giami, and in the Sexual Script Theory, proposed by John Gagnon. For data collection it has been carried out 35 interviews with Nurses of the Family Health Program of the city of Campina Grande (Paraíba, Brazil) with questions to characterize the participants and the following central question: "Tell me about sexuality, based on your life experiences, including professionals. Say what you think the way you want", the same professionals has been invited to participate in the focus groups with the following central question: "How are issues that involve sexuality in health practices in the professional context?" Questions were inserted at a glance when the issues raised were not dealt with in depth by the interviewee or the group, with 21 participants. The data were organized by using the software MAXQDA® Standard 12. The analysis was based on Structural Analysis of Narration. Results: The analysis of the participants’ trajectories has allowed the identification of Sexual’s Scripts in childhood, adolescence and in the professional undergraduation course, presented by stereotypes which results in barriers to prevention of STI/HIV. The Nurses’ interpretation are organized in of sexuality representations as synonymous of sexual relation, sex and gender stereotypes and sexuality, those as a part social imaginary, turn into difficult to deal with the theme, becoming it absent in the Health Care Assistance at Health Family Program Units. The representation about prevention of STI/HIV are based on the representation of illness and gender stereotypes and sexuality, which causing problems for communication with the users and leading to strictly practices in relation to the public and to the implemented stratregies. It has been verified that Nurses who has cultural apprenticeship which cooperate to deconstruct myths and taboos about sexuality, besides, those individuals show a disposition to include approaches about sexual practices an STI/HIV for the users. It can be concluded that these representations about sexuality, learned throughout life, follow scripts translated as barriers to communication about sexuality and to the prevention of STI/HIV in primary health care. The results show that is necessary to change the Nursing Practice in order to introduce Sexuality and Sexual Health as fundamental for Comprehensive Healthcare Policy. It is necessary to invest in processes that take into account Nurses’subjectivies and deconstruct stereotypes presented in the interpretations of professional practices, resulting in improvement for prevention of STI/HIV.